Ketahanan Gizi sebagai Prediktor Kelelahan pada Pasien Kanker Selama Kemoterapi: Studi Kohort Prospektif - Alexander (Program Studi Keperawatan Universitas Jambi, 2025)
Cancer-related fatigue (CRF) is one of the most burdensome symptoms during chemotherapy, yet effective predictors for its trajectory remain limited. While diet quality and food insecurity have been studied separately, the integrated concept of nutritional resilience, the ability to sustain adequate nutrition through stable food access, healthy dietary patterns, and adaptive eating behaviors has not been systematically examined. This study evaluated whether a Nutritional Resilience Index (NRI) predicts fatigue outcomes in cancer patients undergoing chemotherapy in Medan, Indonesia. A prospective cohort study and consecutive sampling was conducted among 200 adults with solid tumors across two tertiary hospitals. Baseline NRI was derived from three domains: food security (HFIAS), dietary quality (AHEI-2010), and adaptive food management strategies. Fatigue was assessed at baseline, post-cycle 2, and post-cycle 4 using the FACIT-F scale. Hierarchical linear regression tested the predictive value of NRI on fatigue trajectories, adjusting for demographic and clinical covariates. Participants (mean age 52.3 ± 11.6 years; 64% female) showed moderate baseline fatigue (FACIT-F 29.8 ± 8.6). Fatigue worsened significantly over chemotherapy (24.1 ± 9.4 at cycle 4, p<0.001). Regression analysis demonstrated that higher baseline NRI predicted significantly lower fatigue scores at cycle 4 (β = −0.31, p<0.001), independent of age, sex, cancer stage, and baseline fatigue. The model explained 42% of variance in fatigue outcomes (adjusted R² = 0.42). Nutritional resilience independently predicts CRF during chemotherapy. Screening and strengthening nutritional resilience may complement guideline-based fatigue management by addressing diet quality, food access, and adaptive eating behavior simultaneously.